2013
DOI: 10.4238/2013.december.16.5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute mountain sickness in young adults at 3200 meters: comparison of the Lake Louise Scoring and Chinese Scoring Systems

Abstract: ABSTRACT. The purpose of this study was to compare two scoring systems used for the diagnosis of acute mountain sickness (AMS): the Lake Louise Scoring (AMS-LLS) and the Chinese Scoring Systems (AMS-CSS). In total, 339 healthy young adult volunteers residing at sea level ascended to 3200 m by train and bus over a total journey time of 48 h. All subjects ascended in the same manner and were divided into three groups that were assessed after one (N = 88), two (N = 91), and three (N = 160) nights, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…However, due to the different symptoms and weights assigned, the incidence determined by the CAS assessment was higher than that by the LLS (59.3% vs 37.5%). This was consistent with previous studies [8,9]. The CAS had diagnostic accuracy for moderate and severe AMS similar to those of the LLS (16.9% vs 17.2%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, due to the different symptoms and weights assigned, the incidence determined by the CAS assessment was higher than that by the LLS (59.3% vs 37.5%). This was consistent with previous studies [8,9]. The CAS had diagnostic accuracy for moderate and severe AMS similar to those of the LLS (16.9% vs 17.2%).…”
Section: Discussionsupporting
confidence: 92%
“…[25] [26] [27] [11] Some Chinese scholars have studied the difference between the LLS and CAS in de ning AMS. Chen et al [9] surveyed 339 males residing at sea level who travelled by train and car to 3200 m. Wu et al [8] surveyed 58 males who went by train and recorded the AMS incidence when they reached different altitude sites, ending at 3658 m. They found that CAS outcomes were in good agreement with LLS outcomes and can accurately diagnose AMS, suggesting that combining the LLS and the CAS in applications of clinical diagnosis can more objectively diagnose AMS than one scoring system alone.…”
Section: Discussionmentioning
confidence: 99%
“…In past studies, researchers have obtained different diagnosis results using the LLS. Vardy et al's 13 study indicated an AMS prevalence of 10% from 3000 to 4000 m, and Chen et al 19 found an AMS prevalence of 17.11% in 339 subjects at 3200 m. Newcomb et al 21 reported that 21% of subjects suffered AMS at 4470 m, and Van Roo et al's 14 study reported that 77.3% of subjects suffered AMS at 6962 m in Aconcagua. The prevalence of AMS assessed by the CAS was 60.3% in Tanggula and 63.8% in Lhasa.…”
Section: Discussionmentioning
confidence: 99%
“…Acute mountain sickness is a syndrome due to the rapid ascending to high-altitude in aviators and mountaineers [4][5][6]. It may be a serious health problem especially in physically inactive subjects.…”
mentioning
confidence: 99%